Budowanie kapitału społecznego przez biblioteki akademickie - Wojciechowska, Maja (Biblioteka Uniwersytecka w Poznaniu, 2018)
Współczesne biblioteki naukowe stają przed nowymi wyzwaniami, które są wynikiem zmiany społeczeństwa – jego kształtu, struktury, zwyczajów, potrzeb i wreszcie oczekiwań. Zmiany te implikują innowacje biblioteczne, niezbędne dla sprawnego funkcjonowania tych instytucji. Biblioteki naukowe, do tej pory związane przede wszystkim z macierzystym środowiskiem naukowym i świadczące na jego rzecz usługi informacyjne, coraz częściej otwierają się na klientów zewnętrznych, tworząc zasoby kapitału społecznego. W artykule przedstawiono zagadnienie kapitału społecznego oraz rolę i znaczenie bibliotek akademickich w jego budowaniu.

Modern research libraries currently face challenges resulting from changes in essential components of society – its shape, structure, customs, needs, and ultimately its expectations. Furthermore, these changes call for innovation in libraries and are necessary for their efficient operation in these new challenging circumstances. Research libraries, hitherto linked primarily to the research environment of their parent institutions and servicing and supporting the latter’s information needs, are becoming more and more directed to the public at large and external clients, and propose ideas and solutions aimed at creating new resources of social capital. This article discusses the social capitalbuilding that involves libraries and the role and significance of academic libraries in the process.
Academic libraries’ contribution to the creation of social capital
Keywords: biblioteki akademickie; academic libraries; kapitał społeczny; social capital; funkcje bibliotek; library functions